Proximate Mechanisms and the Development of Adaptive Memory. (February 2013) - Howe, Mark L.; Otgaar, Henry
Scientific investigations into the functional properties of memory have recently undergone a rapid increase. These studies have revealed that processing stimuli for its survival value results in superior memory performance in children and adults. In this article, we critically evaluate this claim and conclude that survival-processing advantages in childhood and adulthood are not an indication that fitness-relevant information has adaptive priority. Instead, we argue that general memory principles (e.g., item-specific and relational processing, self-referential processing, elaboration and distinctiveness processing) better explain the adaptive function of memory. We stress the importance of these memory processes because they characterize the evolutionary adaptations of memory, are present early in life, and are developmentally invariant.